2003
DOI: 10.1038/sj.bmt.1704029
|View full text |Cite
|
Sign up to set email alerts
|

The degree of matching at HLA-DPB1 predicts for acute graft-versus-host disease and disease relapse following haematopoietic stem cell transplantation

Abstract: Summary:The importance of matching for HLA-DPB1 in unrelated donor haematopoietic stem cell (HSC) transplantation is little understood. Most transplant centres do not, currently, prospectively match for DPB1, but emerging data show that DPB1 matching does play a role in determining outcome. We studied the impact of HLA-DPB1 matching on outcome in 143 recipients of T-cell depletion transplants, who matched with their respective unrelated donors (allelic level) at HLA-A, -B, -C, -DRB1 and -DQB1. Of those matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 29 publications
5
50
2
Order By: Relevance
“…29 Although HLA-DP incompatibilities are very frequent in unrelated donor/recipient combinations, our data do not exclude the possibility that DP-mismatches also contribute to GVHD and mortality. 30 What could be the reason that in spite of the high quality of HLA-typing, there is still no broad consensus on the relevance of single locus-mismatches? It could be that the groups analyzed differ according to the selection criteria of each transplantation center.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although HLA-DP incompatibilities are very frequent in unrelated donor/recipient combinations, our data do not exclude the possibility that DP-mismatches also contribute to GVHD and mortality. 30 What could be the reason that in spite of the high quality of HLA-typing, there is still no broad consensus on the relevance of single locus-mismatches? It could be that the groups analyzed differ according to the selection criteria of each transplantation center.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Shaw et al studied the importance of HLA- International Journal of Hematology and Oncology DP matching in recipients of T-cell depleted unrelated ASCTs. 11 In this study, a significant decrease in aGVHD and higher relapse rate was observed in fully matched HLA-DPB1 ASCTs. But there was no significant difference in engraftment times and OS.…”
Section: Discussionmentioning
confidence: 71%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For instance, in the study by Loiseau et al reported increased frequency of severe aGVHD and poorer survival in two HLA-DP incompatibilities in a group of unrelated ASCT patients. 10 In this study they were not able show a significant relationship between HLA-DP mismatches and disease relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Bronwen Shaw began by providing a summary of her work at the ANRI and the ANT experience in this area. [2][3][4] She presented data on 423 UD-HSCT performed between 1996 and 2003 for whom four digit molecular tissue typing for 12 alleles and clinical follow-up data were available. The percentage of wellmatched (10/10) donor-recipient pairs (67%) in the ANT study was greater than that in any other study (44% in the Japanese Marrow Donor Programme study 5 and 47% in the Fred Hutchinson Cancer Research Center study 6 ), in part due to the time period over which the study was performed.…”
Section: Donor Selection and Transplant Outcomementioning
confidence: 99%